The Effect of Using Multimedia Application in Language Issues to Increase Vocability of Deaf Children Class III SLB B YRTRW Surakarta 2018-2019 - Subroto, Alfath Nuur Fajar Wahyu (Indonesian Journal of Disability Studies, 2019)
This research aims to the effective use of application multimedia sign language to enhancement vocabulary deaf children class III SLB B YRTRW Surakarta in year 2018/2019. This research use pre-experimental design has the form of one group pretest-posttest design.Â  A subject in this research such as 7 children deaf class III in SLB B YRTRW Surakarta 2018/2019 that determined use by surfeited sampling. The instrument research use guide oral test with answer the direct question from the question that given by the Â researcher. Data of research analyzed use by Wilcoxon Sign Rank Test.Based on data analysis that was done, the value of Zhitung = -2,366 with asymp.sig.(2-tailed) is 0,018 that under significance level (p < 0,05). That result shows that application multimedia sign language takes effect to increase vocabulary deaf children class III in SLB B YRTRW Surakarta in year 2018/2019.